The integration of holistic education and multiple intelligences - Baasiri, Bassima Kamel (Beirut, 2013)
The study examines the modifications at Hariri preschool in a way to reflect the integration of a holistic approach with multiple intelligences' activities. These activities were designed to elicit from children meaningful experiences related to his/her environment. It aims at bringing up a whole child in a way that does not only promote the cognitive developmental skills but also the physical, socio-emotional and aesthetic developmental skills.
: Chapter in a Book
Keywords: Intelligence multiple; Méthodes d enseignement; Multiple Intelligence; Teaching Methods